Note from the editor: Inequality and wealth in Latin America - Mariana Heredia (economic sociology. perspectives and conversations, 2023)
For many analysts, Latin America has long stood out as one of the most unequal regions in the world. However, according to Juan Gabriel Palma, in recent decades this characteristic is less a hangover from the past than the destiny to which many developed countries seem to be heading. In his words, "as far as inequality is concerned (and not just inequality!), now it is the highly unequal middle- income countries that show the more advanced ones 'the image of their own future'" (Palma 2016, 7).
Keywords: 300